ONLINE POLITICAL CAMPAIGNS REGARDING PUBLIC OPINION MANIPULATION FROM A CONSTITUTIONAL LAW PERSPECTIVE [HTN] - Yuliana Menai; Adensi Timomor; Meiske M. W. lasut (Judge : Jurnal Hukum, 2025)
The development of digital technology has brought about major changes in the way political campaigns are conducted. Campaign activities that were previously carried out conventionally have now shifted to the online realm. This change has had a significant impact on the democratic process, particularly in the context of public opinion manipulation. This study focuses on analyzing law enforcement and the role of constitutional law regulations in regulating and preventing manipulative practices in digital-based political campaigns. The research method used is a normative legal approach by examining various laws and regulations, such as the Election Law, the Electronic Information and Transaction Law (ITE), and regulations issued by the General Election Commission (KPU) and the Election Supervisory Agency (Bawaslu). The findings show that manipulation of public opinion is often carried out in various ways, including the spread of disinformation, the use of fake identities or anonymous accounts, the use of bots, and the application of deepfake technology. In practice, law enforcement efforts against these acts still face various obstacles, such as weak regulations specifically governing digital manipulation, limited law enforcement resources, and difficulties in tracking perpetrators operating in cyberspace. Therefore, it is necessary to update regulations that are responsive to technological developments, improve the competence of election supervisory agencies, and strengthen digital literacy in society. These steps are expected to serve as preventive strategies to realize healthier, more transparent, and democratic political campaigns.